METODE TOTAL PHYSICAL RESPONSE (TPR) TERHADAP PENGUASAAN KOSAKATA ANAK TUNARUNGU TK/KB - Sandhy, Noor (Jurnal Pendidikan Khusus, 2017)
Abstract: Deafness causes problems in some aspects including, physical and language problems, intelligence, social and emotional, and personality. Among these aspects of developmental problem, language development is a major problem that needs attention. The problem in the language development is the result of the limited language acquisition and vocabulary, and therefore it is needed a  methods that can help  children to improve their mastery of vocabulary. The learning method which is used to increase the vocabulary of deaf children in this study were using Total Physical Response (TPR) with steps namely; (1) Teaching and Learning, (2) Practice and Exercise, and (3) Evaluation and Repetition. Vocabulary aspect which is studied is a passive-receptive vocabulary and active-productive vocabulary.The subjects in this study is six  5-7 years old deaf children in the TK/ KB Aurica Surabaya. The aim of research to examine the effect of the Total Physical Response (TPR) method toward deaf children vocabulary TK / KB Aurica Surabaya. This study uses quantitativ eapproach with the type of research is Pre Experiment, using the research design One Group Pre - test Post - test Design to obtain data on the ability of deaf children vocabulary before and after a given treatment.The results were obtained from the pre-test and post-test results. It is resulted, pre-test results of 62, 33 and post-test results 86.15. Thus it can be concluded that Zcount = 2.05 compared with 5% Ztable crisis value = 1.96. Results showed that greater than Ztable Zcount (Zh> Zt) which means that Ho refused and Ha is received so that it can be said there is the effect of the Total Physical Response (TPR) method of the vocabulary of deaf children in TK/ KB Aurica Surabaya.   Keywords: Total Physical Response (TPR) Methods, Vocabulary Mastery.